Computational metrics for soccer analysis : connecting the dots /: connecting the dots. ([2018]) - Clemente, Filipe Manuel; Sequeiros, João Bernardo; Correia, Acácio F. P. P; Silva, Frutuoso G. M; Martins, Fernando Manuel Lourenço
No abstract available